Inferring causal effects of homocysteine and B-vitamin concentrations on bone mineral density and fractures: Mendelian randomization analyses - Fu, Liwan; Wang, Yuquan; Hu, Yue-Qing (Frontiers in Endocrinology, 2022)
Objectives: In the progress of bone metabolism, homocysteine (Hcy) and B vitamins play substantial roles. However, the causal associations of homocysteine, B vitamins concentrations with bone mineral density (BMD) and fractures remain unclear. Therefore, we employed a two-sample Mendelian randomization (MR) design to infer the causal effects of Hcy and B vitamins on BMD and fractures. Methods: We selected instrumental variables from large genome-wide association studies (GWAS). Specifically, the exposures mainly included Hcy (sample size: 44,147), vitamin B12 (sample size: 45,576), folate (sample size: 37,465), and vitamin B6 (sample size: 1864). The outcome variables included total body BMD (sample size: 66,628), heel BMD (sample size: 142,487), femoral neck BMD (sample size: 32,735), lumbar spine BMD (sample size: 28,498), and forearm BMD (sample size: 8143). Additionally, total body BMD in several age strata was also included. Furthermore, fractures of the forearm, femoral neck, lumbar spine and heel corresponding with the BMD regions were added as additional outcomes, which encompassed 361,194 subjects, with 8438 cases. Two-sample MR approaches were utilized in this study. The inverse variance weighting (IVW) was adopted as the main analysis. MR-PRESSO, MR-Egger, weighted median estimate, and Multivariable MR were performed as sensitivity methods. Results: In the main analysis, Hcy concentrations have inverse association with heel BMD (Beta = 0.046, 95% confidence interval (CI) -0.073 to -0.019, P = 9.59E-04) for per SD unit. In addition, for one SD increase of vitamin B12, the total body BMD decreased 0.083 unit (95%CI -0.126 to -0.040, P = 1.65E-04). The trend was more obvious in age over 45 years (Beta = -0.135, 95%CI -0.203 to -0.067, P = 9.86E-05 for age 45-60; Beta = -0.074, 95%CI -0.141 to -0.007, P = 0.031 for age over 60 years). No association of B vitamins and Hcy levels with risk of fractures was found in this study. Other sensitivity MR methods elucidated consistent results. Conclusions: Our findings indicated that there exist inversely causal effects of Hcy and vitamin B12 on BMD in certain body sites and age strata. These give novel clues for intervening bone related diseases in public health and nutrition.